Impact of certification on market performance of cocoa industry in OSUN State, Nigeria - Taiwo Fausiyat Adesiyan; Olufemi Adedotun Yesufu; Ayodeji Damilola Kehinde (Social Sciences and Humanities Open, 2023)
This study investigated the effect of certification on the market performance of the cocoa industry using primary data from a cross-sectional survey of 240 cocoa marketers. Considering counterfactual scenarios, this study analyzed the effects of certification on the net marketing margin of cocoa marketers using the endogenous switching regression model (ESRM) and for the robustness evaluation, inverse-probability-weighted regression adjustment (IPWRA) was utilized. Results showed that about 92% of the cocoa marketers were Licensed Buying Agents (LBAs) then the exporter (7%) and the least were cooperatives with about 3%. The results showed that 28% of the Licensed Buying Agents (LBAs) were certified while 35% of the exporters were certified. Also, the results revealed that 3 different marketing channels were used in the study area. The cost and return analysis revealed that certified marketers are efficient and more productive in their business compared to uncertified marketers. The ESRM treatment impact suggested that the average net marketing margin of certified cocoa marketers is higher than those that were uncertified. The study concluded that certification has helped to improve the marketing of cocoa marketers in the study.